The Determinants Of Renewable Energy Consumption: An Empirical Analysis For The Balkans - Akar, Basak Gul (European Scientific Journal, ESJ, 2016)
As a measure of development, energy has a priority in economic literature. However, both economic and social costs caused by traditional energy sources have led to question on the importance of these resources. In addition to this, various problems such as pollution and dependence on foreign energy has brought about new researches instead of existing energy sources. Alternative and renewable energy sources, which are named as “clean energy”, are expected to take the place of the old method. However, there are many factors affecting the use of new energy sources. These factors include energy prices, energy production, energy dependence, economic growth, trade openness, and the use of carbon dioxide. Besides, development levels of countries have a significant influence on the degree of interaction between these factors. In the present study, firstly, renewable energy consumption and the determinants of this energy use were discussed in the theoretical context. Consequently, the required empirical tests were applied for Balkan countries - Albania, Bosnia-Herzegovina, Bulgaria, Croatia, Montenegro, Kosovo, Macedonia, Romania, Serbia, Slovenia, Turkey, and Greece. Dynamic panel data method was preferred for analysis. However, this panel covers a period between the years of 1998-2011. According to the results obtained through a dynamic panel data analysis, it was found that there is a negative and statistically significant relationship between economic growth and renewable energy consumption. On the other hand, trade openness and natural gas rents are determined to have a positive effect on renewable energy consumption in the Balkans.